A New Algorithm for Literature Recommendation Based on a Bibliographic Heterogeneous Information Network. Issue 4 (1st July 2018) - Li, Linna; Wang, Lijun; Jiang, Xueqin; Han, Hongqi; Zhai, Yun
Abstract : A literature recommendation algorithm based on a heterogeneous information network is proposed. The proposed algorithm can process different types of semantic information and implicit feedback. The experimental results show that the proposed algorithm can provide more effective recommendations than those algorithms without employing these semantic information and implicit feedback.